Don't know much about mythology [compact disc, unabridged] : everything you need to know about the greatest stories in human history but never learned - Davis, Kenneth C. (Random House Audio, 2005)
With humor and wit, the tales of the great myths of the world are explained as is their relevance to current movies, art, language, and music.